1998
DOI: 10.1210/jcem.83.3.4672
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Functional Nongenomic Progesterone Receptors on Human Sperm Membrane1

Abstract: The presence of functional nongenomic progesterone (P) receptors in human spermatozoa has been investigated by equilibrium binding studies in intact spermatozoa, ligand blot and Western blot analysis of sperm lysates, as well as determination of the effects of the steroid on sperm intracellular Ca 2ϩ concentrations. Binding experiments were performed using progesterone-11␣-glucuronide-[125 I]iodotyramine as tracer. Computer analysis of competition curves using different steroids as competitors indicated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 39 publications
(31 reference statements)
2
15
1
Order By: Relevance
“…However, all of the proteins which are possibly translated from the PR isoform S mRNA have various lengths of the carboxy terminal part of the progesterone-binding domain of the iPR and lack the amino terminal and DNA-binding domains. This putative structure of the proteins encoded by the PR isoform S mRNA correspond to that of the mPR in the Sp as indicated in previous reports which revealed that the sperm mPR possessed the carboxy terminal part of the progesterone-binding domain but not the amino terminal- and DNA-binding domains [7, 9, 10]. On the other hand, the calculated molecular weight of the longest protein encoded by the isoform S transcript, which utilizes codon 691 (indicated by the double underlining in fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…However, all of the proteins which are possibly translated from the PR isoform S mRNA have various lengths of the carboxy terminal part of the progesterone-binding domain of the iPR and lack the amino terminal and DNA-binding domains. This putative structure of the proteins encoded by the PR isoform S mRNA correspond to that of the mPR in the Sp as indicated in previous reports which revealed that the sperm mPR possessed the carboxy terminal part of the progesterone-binding domain but not the amino terminal- and DNA-binding domains [7, 9, 10]. On the other hand, the calculated molecular weight of the longest protein encoded by the isoform S transcript, which utilizes codon 691 (indicated by the double underlining in fig.…”
Section: Resultssupporting
confidence: 67%
“…1) of iPR as the start codon, is approximately 29 kD. The weight was lower than that in the two previous reports; Sabeur et al [7]indicated approximately 54 and 57 kD [7], and Luconi et al [9]reported approximately 50 and 52 kD [9]. Therefore, we cannot conclude that the protein(s) encoded by the PR isoform S mRNA is the sperm mPR at the present time.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Currently, three types of receptors present in the human spermatozoa have been described to mediate the action of P in these cells: (1) a GABA A -like receptor Winstrom & Meizel (1993); (2) a receptor with partial homology to the intracellular progesterone receptor Luconi et al (1998), and (3) a receptor with partial homology to the liver porcine endomembrane receptor Buddhikot et al (1999). Binding of P to its receptor stimulates the AR through a mechanism involving a rapid and transient increase in intracellular Ca 2+ concentration, because of Ca 2+ in¯ux from the extracellular medium Blackmore et al (1990), Thomas & Meizel (1989).…”
Section: Discussionmentioning
confidence: 99%
“…In human decidua two bands were observed, at 45 and 36 kDa corresponding to different isoforms of the progesterone receptor [51]. A non-classical form of PR involved in the opening of calcium channels in the mitochondrial and cellular membranes has been characterized in the cytoplasmic membranes of human sperm [52,53] with molecular weights ranging from 25 to 85 kDa [49]. The well established membrane progesterone receptor found in fish was cloned and found to have a molecular weight of 40 kDa [54].…”
Section: Discussionmentioning
confidence: 99%